Admission high-sensitivity cardiac troponin versus a biochemical score for predicting mortality in patients with COVID-19 (2020)
Emerging evidence indicates a role for cardiac troponin testing, specifically high-sensitivity cardiac troponin (hs-cTn) in hospitalized patients with COVID-19(1). Undetectable levels of hscTn in patients with (and without) COVID-19 may be helpful in identifying a low-risk subgroup, with higher levels useful in identifying patients at high-risk for hospital death(1,2). Further improvements in risk-stratification for emergency department or hospitalized patients may be achieved by adding clinical chemistry tests, such as glucose and creatinine [i.e., estimated glomerular filtration rate (eGFR)] to generate a clinical chemistry score (CCS)(2,3). For patients with COVID-19, additional biochemical tests may have important prognostic roles such as urea which is already a component of the CURB-65 score (confusion, urea, respiratory rate, blood pressure, age ≥65y) used to risk stratify patients presenting to hospital with pneumonia(4). We performed a retrospective chart review of COVID-19 patients admitted to hospitals in the city of Hamilton in order to explore the performance characteristics of hs-cTn levels, the CCS and the CCS with urea (CCUS) to predict in-hospital death. This review included the first 26-weeks of this pandemic (ethics-approval:#11425-C).